Prevalence of serum anti-neuronal autoantibodies in patients admitted to acute psychiatric care. Issue 16 (9th September 2016) - Schou, M.; Sæther, S. G.; Borowski, K.; Teegen, B.; Kondziella, D.; Stoecker, W.; Vaaler, A.; Reitan, S. K.
Abstract : Background: Autoimmune encephalitis associated with anti-neuronal antibodies may be challenging to distinguish from primary psychiatric disorders. The significance of anti-neuronal antibodies in psychiatric patients without clear evidence of autoimmune encephalitis is unknown. We investigated the serum prevalence of six anti-neuronal autoantibodies in a cohort of unselected patients admitted to acute psychiatric care. Method: Serum was drawn from 925 patients admitted to acute psychiatric in-patient care. Psychiatric diagnoses were set according to International Classification of Diseases (ICD)-10 criteria. Antibody analysis was performed with an indirect immunofluorescence test for N -methyld -aspartate receptor (NMDAR) antibodies and five other anti-neuronal autoantibodies of the immunoglobulin (Ig) classes IgA, IgG and IgM isotype. Results: Anti-neuronal autoantibodies were found in 11.6% of patients: NMDAR antibodies in 7.6%, contactin-associated protein-like 2 (CASPR2) antibodies in 2.5%, glutamic acid decarboxylase-65 (GAD65) antibodies in 1.9%, and α -amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor antibodies in 0.1%. Leucine-rich glioma-inactivated protein-1 (LGI1) and γ -aminobutyric acid B (GABAB ) receptor antibodies were not detected. NMDAR antibodies of class IgG were present in five patients only (0.5%). NMDAR antibodies of all Ig classes were equally prevalent in patients with and without psychosis. There were no significant differences in antibody prevalence in the different diagnostic categories, except for a higher odds ratio of being NMDAR antibody positive for patients without a specific psychiatric diagnosis. Conclusions: NMDAR IgG autoantibodies, which are known to be strongly associated with anti-NMDAR encephalitis, were rarely found. CASPR2 and GAD65 antibodies were more frequently encountered in the present study than previously reported. Further research on the clinical significance of anti-neuronal autoantibodies in patients with acute psychiatric symptoms is needed.